PARASITOLOGICAL INDICATORS OF FOOD SAFETY - S.A. SHEMETOVA; R.S. ARAKELYAN; N.V. POLYANSKAYA; G.L. SHENDO (Avicenna Tajik State Medical University, 2021)
Objective: Study and assess food safety by parasitological indicators for 2010-2019. Methods: Documents of the Center for Hygiene and Epidemiology in the Astrakhan region were used in this study Results: Among a total of 9610 samples examined within the test period (2011-2019) of the general parasitological sanitary studies, food samples comprised 10.6%, with 1% prevalence of parasitic pathogens. Among the food samples the highest portion (54%) were horticultural products (fruits, vegetables, table greens, berries, juices) with 1.7% prevalence of parasitic contamination. In addition to horticultural products, fish and fish samples were examined, accounting for 29% of samples, of which 0.1% were contaminated with helminths. Meat and meat product foodstuffs samples were also examined during the investigation period (17%) and all samples examined met the sanitary standards. Conclusion: Parasitic contamination of foodstuffs continues to be intense, as shown by the above indicators. The presence of helminth eggs and larvae on the surfaces of horticultural products indicates either their contamination by human and/or animal feces, or the direct contact of fruit and vegetable products with contaminated soil. The presence of helminths in fish is a potential threat to public health.